Association between HIV-2 infection and genital ulcer diseases among male sexually transmitted disease patients in The Gambia. - Pépin, J; Quigley, M; Todd, J; Gaye, I; Janneh, M; Van Dyck, E; Piot, P; Whittle, H (1992)
OBJECTIVE: To investigate whether genital ulcer diseases are cofactors which enhance the transmission of HIV-2 in West Africa. DESIGN: A cross-sectional study of 435 men presenting with a sexually transmitted disease (STD). SETTING: The outpatient clinic of the Medical Research Council Laboratories, a primary care facility in Fajara, a suburb of Banjul, the capital city of The Gambia (West Africa). PATIENTS, PARTICIPANTS: Six hundred and twenty-four men presenting with a genital complaint, of whom 443 had an STD. Eight of the men with an STD were excluded from further analysis because they were HIV-1-infected (five patients) or had indeterminate Western blot patterns (three patients). The remaining 21 HIV-2-infected and 414 seronegative men constituted our study-group. MAIN OUTCOME MEASURES: Participants were questioned about previous STD and behavioural and demographic characteristics. A physical examination was performed and serum collected for measurement of antibodies against Haemophilus ducreyi and Treponema pallidum. RESULTS: HIV-2-infected men were more likely than HIV-seronegative participants to have previously had a genital ulcer [odds ratio (OR), 3.00; 95% confidence interval (Cl), 1.18-7.60] and to have antibodies against T. pallidum (OR, 5.95; 95% Cl, 2.10-16.91), or H. ducreyi (OR, 4.59; 95% Cl, 1.71-12.33). Circumcised patients with residual foreskin were more likely to be HIV-2 infected than patients with complete circumcision. HIV-2-seropositive patients were six times more likely to have generalized lymphadenopathy than their seronegative counterparts. CONCLUSIONS: Our data suggest that genital ulcerative diseases, such as syphilis and chancroid, are probably cofactors that increase the transmission of HIV-2 in West Africa, and that HIV-2 infection frequently results in generalized lymphadenopathy.